Citric acid assisted Fenton-like process for enhanced dewaterability of waste activated sludge with in-situ generation of hydrogen peroxide. (1st September 2018) - Xiao, Keke; Pei, Kangyue; Wang, Hui; Yu, Wenbo; Liang, Sha; Hu, Jingping; Hou, Huijie; Liu, Bingchuan; Yang, Jiakuan
Abstract: Fenton's reagent has been widely used to enhance sludge dewaterability. However, drawbacks associated with hydrogen peroxide (H2 O2 ) in Fenton's reagents exist, since it is a hazardous chemical and shows carcinogenicity, explosivity, instability, and corrosivity. Moreover, initial acidification and subsequent neutralization are needed as optimal conditions for homogeneous Fenton conditioning and final filtrate discharge. In this study, a Fenton-like process for the enhanced dewaterability of waste activated sludge with in-situ generation of H2 O2 and without extra pH adjustment was firstly proposed, namely citric acid (CA)-assisted oxygen activation in an air/nano zero-valent iron (nZVI) system and chemical re-coagulation with polydiallyldimethylammonium chloride (PDMDAAC). Using the response surface methodology (RSM), the optimal doses of CA, nZVI, and PDMDAAC were determined to be 13, 33, and 9 mg g −1 dry solids (DS), respectively. This composite conditioner showed a good dewatering capability compared with the raw sludge, e.g. the capillary suction time decreased from 130.0 to 9.5 s. The enhanced sludge dewaterability was further confirmed by laboratory-scale diaphragm filter press dewatering tests, which produced a lower cake moisture content compared with the raw sludge, and the final pH of the filtrate was close to neutrality. The citric acid promoted the production of H2 O2 and Fe(II)/Fe(III) species, the degradation of protein in tightly-bound extracellular polymeric substances, and the decomposition of protein-N in the solid phase of sludge, resulting a greater conversion of bound water to free water. The results of electron spin resonance indicated that the hydroxyl radicals were mainly responsible for the decomposition of proteinaceous compounds. The subsequent chemical re-coagulation with PDMDAAC can make the zeta potential of sludge samples less negative, reduce the repulsive electrostatic interactions, and agglomerate the smaller particles into larger aggregates, thus enhancing sludge dewaterability. Graphical abstract: Image 1 Highlights: A novel conditioner of air/CA/nZVI/PDMDAAC was used for sludge dewatering. CST significantly decreased from 130.0 to 9.5 s at optimal conditions. In-situ H2 O2 and OH were generated in the pre-oxidation to release bound water. Without extra adjustment, pH of the final filtrate can be close to neutrality. A two-step mechanism was proposed for air/CA/nZVI/PDMDAAC conditioning.